Neurodegenerative Diseases, Psychiatric Conditions, and Cancer: Interconnections and Shared Pathways - Mohd Sharique Katchhi; Aaliya Oomatia; Bhoomika S Bhandari; Deeksha N; Bhagya V Rao (International Journal of Indian Psychȯlogy, 2024)
This article explores the complex interaction and shared pathways between neurodegenerative diseases, psychiatric conditions, and cancer. Alzheimer’s disease (AD) and cancer share mechanisms such as apoptosis and oxidative stress, showing an inverse correlation, with AD patients having a reduced cancer risk. Parkinson’s disease (PD) and cancer demonstrate complex interplays, with PD patients showing reduced risks for certain cancers but increased risks for melanoma and brain cancer. Schizophrenia (SZ) is linked to breast cancer through genetic and immunological pathways, while epilepsy often co-occurs with brain tumors, with seizures arising from neoplasms or cancer treatments. Anxiety and depression are prevalent in cancer patients, affecting their prognosis and quality of life. Insomnia significantly worsens cancer patients’ quality of life, exacerbated by treatments and stress. Lastly, while bipolar disorder (BD) and cancer connections are influenced by lifestyle factors and medication effects, recent studies show no increased cancer risk in BD patients.